Pendampingan Bendahara Sekolah di Lingkungan “Yayasan XXX Cabang Kota Jayapura” dalam Melatih Penyusunan Laporan Keuangan Nir Laba sesuai ISAK 35 Berbasis Microsoft MS Excel 2019 - Muthmainnah Muthmainnah; Fahrudin Pasolo; Mukti Stoffel; M. Ridwansyah Pasolo; Ismail Noy (Jurnal Pengabdian Masyarakat Nusantara, 2024)
Public sector Financial Reporting has undergone changes in the standards used. Currently, ISAK 35 has been determined as a replacement for PSAK 45 which is oriented to the Non-Profit Entity Consortium Report. The XXX Foundation Jayapura City Branch is promoting computerization of financial reporting through MS Excel 2019. For this purpose, this community service is carried out to school principals and school treasurers (daily and BOS) in order to be able to produce computerized-based financial reports in accordance with ISAK 35 as a form of financial accountability and transparency within the XXX Foundation Jayapura City Branch. The results show that the Preparation of School Financial Statements through MS Excel 2019 Media has succeeded in achieving its main goal, which is to increase participants' understanding of ISAK 35 accounting standards and their practical application in compiling financial statements using MS Excel. This activity contributes in the form of increasing transparency and accountability in the preparation of reports, improving participants' ability to understand and implement accounting standards, and increasing public trust and supporting the school's operational and strategic success.